Analysis of the Influencing Factors on Electrical Properties and Evaluation of Gas Saturation in Marine Shales: A Case Study of the Wufeng-Longmaxi Formation in Sichuan Basin - Sun, Fujing; Sun, Jianmeng; Zeng, Xin; Yuan, Weiguo; Zhang, Jinyan; Yan, Wei; Yan, Weichao (Frontiers in Earth Science, 2022)
Accurate gas saturation calculations are critical to evaluating the production of marine shale gas reservoirs. As a high-resolution exploration method, geophysical resistivity well-logging technology has been widely applied in almost all types of oil/gas reservoirs to evaluate formation fluid saturation. Although the calculated saturations are accurate for conventional reservoirs, it is a challenging task to acquire the gas saturation of shale gas reservoirs due to the presence of complex rock compositions and fluid types. It is necessary to analyze different influencing factors on electrical properties to establish a more applicable gas saturation model for marine shales. In our research, we made full use of geological data, well logging data, and rock experiment data to analyze the influencing factors of electrical properties in the Wufeng-Longmaxi Formation in the Sichuan Basin, China. Six conductive factors were studied, including stratigraphic structures, clay minerals, pyrite, organic matter, pore structures, and formation fluids. Then, a shale conductivity model was developed, in which high- and low-resistivity layers were connected in parallel. Based on the conductivity model, a new method for influencing factors of stepwise stripping conductivity was proposed to calculate shale gas saturation. Finally, by interpreting the well logging data of two shale gas wells, we compared the saturation calculation results of different methods to demonstrate the accuracy of the new method. The results show that thin, low-resistivity layers, clay minerals, pyrite and overmature carbonized organic matter reduce the resistivity of shale and weaken the contribution of fluids to the measured shale resistivity. Moreover, the calculation accuracy of this new method was better than that of Archie’s equation, Simandoux’s equation and the neutron-density porosity overlay method. The findings of this paper will help gain insight into the mechanism of resistivity responses for marine shale reservoirs and improve the accuracy of the estimated gas saturation.